The Evaluation of Dialysis Adequacy by KT/V in Hemodialysis Patients - Seyed Seifollah Beladi Mousavi; Khojaste Hosaini Nejad; Abbas Ali Zeraati (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Patients with ESRD need adequate dialysis. According to DOQI guidelines, minimum dialysis dose by KT/V in patients under hemodialysis (HD) is 1.2 or greater. Subjects and Methods: In a cross- sectional study, we evaluated the value of KT/V among HD patients in shahid Beheshti Hospital of Abadan, Iran. HD was performed for 3 to 4 hours, using synthetic dialyzer and the bicarbonate- based dialysate. Blood flow rate, dialysate flow rate and ultrafiltration rate were 250 to 300 cc /min, 500cc/min and zero or 1 to 3 liters, respectively. Blood sampling for BUN was done immediately before and after the dialysis session. We used the following equation to estimate the KT/V from the percent reduction in urea (PRU). KT/V = (0.026 ×PRU) – 0.460Results: 54 HD patients (28 females and 26 males) with the mean age of 39 ± 14.2 years were enrolled in the study. The most common cause of ESRD was hypertension (24.07%) followed by, unknown (22.22%), DM (18.51%), Chronic Glomerulonephritis (14.81%), urinary tract abstraction (12.96%) and poly cystic kidney disease (7.40%). KT/V was less than 1.2 in 87.03 patients (n=47). There was no significant difference in the valve of KT/V in men and women (P= 0.54) and in different hemoglobin concentration (p=0.58). Conclusion: The results of the study show that the most of our HD patients have not received minimum dialysis dose and we should evaluate and correct its causes.